Kinetic modeling of NiO-based oxygen carriers for the sorption enhanced chemical looping steam CH4 reforming. (2018) - Ipsakis, D.; Heracleous, E.; Silvester, L.; Bukur, D.B.; Lemonidou, A.A.
Abstract: The reduction and oxidation (redox) kinetics of four NiO-based oxygen carriers (OCs) under chemical looping conditions are presented and discussed in this study. The 40% NiO OCs were supported on Al2 O3, TiO2, SiO2 and ZrO2 and were isothermally tested in a thermogravimetric unit connected with a mass spectrometer (TGA-MS) in 20 redox cycles (reduction under 15% CH4 /He at 650°C/oxidation under air at 800°C). Several solid-state kinetic models (chemical reaction controlled, geometrical/volumetric contraction, diffusion limited, nucleation growth and random pore models) were consecutively and optimally screened for each OC and for different redox cycles. As was found, metal-support interactions occurring between NiO and Al2 O3, TiO2 supports lead to a reduction controlled by chemical reaction and was quantitatively captured through the "Unreacted Shrinking Core Model". On the contrary, reduction of NiO supported on SiO2, TiO2 is controlled by "nucleation and nuclei growth" and Avrami-Erofeev kinetics fitted the respective experimental data. Regarding oxidation, the present study revealed that it is controlled by nucleation and "Avrami-Erofeev" (NiO/Al2 O3, NiO/TiO2 ) and "Prout-Tompkins" (NiO/ZrO2 ) kinetic models provided an optimal fitting. In all studied cases, the progressing of cycles revealed structural material modification that were summed up to significant variations in OCs' redox rates and related kinetics